The Efficacy of Hypnosis in the Treatment of Chronic Musculoskeletal Pain: A Systematic Literature Review - Taylor, Damian (Auckland University of Technology, 2021)
Hypnosis has a long history of use in the treatment of a variety of physical and psychological conditions. However, its effectiveness as a treatment for chronic musculoskeletal pain and the best method for delivery of the hypnotic intervention is still unclear. Therefore, the objective of this study is to review the research surrounding the efficacy of hypnosis for chronic musculoskeletal pain and to identify the most effective intervention delivery strategies. A systematic literature review was performed using the Scopus electronic database to locate all studies that had used hypnosis with a chronic, musculoskeletal pain condition. Thirteen studies met the inclusion criteria, of which 12 were randomised controlled trials. The total number of participants across the studies was 627, with a mean age of 48.3 years. The number of intervention sessions in the hypnosis group ranged from a single session to 14 weekly sessions, with a mean of seven sessions across the studies. The hypnotic intervention session durations ranged in length from 20 minutes up to 2.5 hours and were predominately given on a weekly basis. Collectively, the included studies provided high quality evidence that hypnosis has a positive effect in reducing pain intensity in chronic musculoskeletal conditions compared to standard care and waitlist controls. When compared to relaxation, differences between groups were less consistent but still tended to favour the hypnotherapy groups. Similarly, when compared to physical interventions such as physiotherapy or trigger point therapy, hypnosis was also shown to be more effective. The addition of hypnosis to other psychologically based interventions, such as cognitive behavioural therapy and pain education, created greater improvements in many outcome measures related to a person’s pain experience, such as average and worst pain intensity, and catastrophising. The studies that used a larger variety of hypnotic suggestions that targeted pain intensity, and the cognitive and emotional components of pain, achieved better outcomes. Hypnosis can, therefore, be recommended as a viable treatment option, either as a stand-alone-treatment or as an adjunct to other psychological interventions for the treatment of chronic musculoskeletal pain. Studies investigating the efficacy of specific components of the hypnotherapy interventions around dosage and delivery methods, with larger populations of a more homogenous sample are required to establish more robust conclusions regarding these parameters in a chronic musculoskeletal pain population.
Keywords: Hypnosis; Chronic Musculoskeletal Pain; Literature Review Pain Management